2016
DOI: 10.21873/anticanres.11244
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PBK/TOPK Contributes to Tumor Development and Poor Outcome of Esophageal Squamous Cell Carcinoma

Abstract: Abstract. Background: PDZ-binding kinase/T-celloriginated protein kinase (PBK/TOPK) is a serine-threonine kinase and overexpressed in various types of cancer. PBK/TOPK is associated with tumor cell development and 58). Knockdown of PBK/TOPK using specific siRNAs inhibited the cell proliferation, invasion/migration of PBK/TOPK-overexpressing ESCC cell lines. Conclusion: These findings suggest that PBK/TOPK plays a crucial role in tumor malignant potential through its overexpression in ESCC.Esophageal cancer is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 24 publications
3
32
3
Order By: Relevance
“…Deregulation of PBK has been reported in other cancer types. Ohashi et al reported that PBK was up-regulated in esophageal squamous cell carcinoma and associated with worse prognosis [ 16 ]. Kwon et al showed that PBK expression in gastric carcinoma was significantly increased and predicted poor overall survival [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of PBK has been reported in other cancer types. Ohashi et al reported that PBK was up-regulated in esophageal squamous cell carcinoma and associated with worse prognosis [ 16 ]. Kwon et al showed that PBK expression in gastric carcinoma was significantly increased and predicted poor overall survival [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with combination of high TOPK and mutp53 had lowest prognosis 63 Haematological Primary AML qRT-PCR, immunoblotting TOPK detected in 9/12 samples; 3/3 ALL samples and in plasmocytoma and blastic type mantle cell lymphoma. Weak expression in peripheral blood stem cells 64 Gastric Gastric carcinoma IHC, immunoblotting Expression independently correlated with poor outcome 65 Oesophageal Oesophageal squamous cell carcinoma qRT-PCR, IHC, immunoblotting Expression independently correlated with poor outcome 66 Colorectal Colorectal carcinoma IHC tissue microarray No relationship between VEGFa gene amplification and TOPK expression/gene status 67 Expression of TOPK in primary tumours is linked to enhanced tumour aggression, invasion and metastatic spread in a variety of cancers. Multivariate analysis of clinical samples from numerous sites indicates that a significant relationship exists between TOPK expression in tumour tissue and poor prognosis for patients.…”
Section: Preclinical Rationale: Topk Overexpression In Cancermentioning
confidence: 99%
“…Because of the heterogenous nature of colorectal cancer, interventions in a range of oncogenic signalling pathways would be a rational approach for developing new therapies. One of the emerging oncogenic signalling molecules is an intracellular protein kinase, the T‐lymphokine‐activated killer cell‐originated protein kinase (TOPK; also known as PDZ binding kinase, PBK), which has been implicated in the development and progression of gastric (Ohashi et al, 2017) and ovarian cancers (Ikeda et al, 2016), oesophageal squamous cell carcinomas (Ohashi et al, 2016), and colorectal cancer (Zlobec et al, 2010).…”
Section: Introductionmentioning
confidence: 99%